Exploration The Quality of Knowledge Sharing in Increasing Employees’ Innovative Behavior - Ratna Pratiwi (Program Studi S3 Ilmu Manajemen, 2021)
Background: Maximizing the innovation potential of employees is a top priority in all companies. New ideas and initiatives generated by employees give the organization a competitive advantage by differentiating and improving products or services. Given the growing importance of intellectual capital in all areas of the company, human resource researchers and professionals are expected to develop and implement effective measures that encourage their employees to innovate. Several factors that can increase employee innovation behavior are the quality of knowledge sharing and its support, namely, employee motivation to learn and transformative leadership. Purpose: This study was intended to examine the direct effect of learning motivation on employee innovative behaviour and the indirect effect of motivation to learn and transformational leadership in improving the quality of knowledge sharing on increasing employee innovative behaviour. Originality/value: The novelty of this research is that there is no research on motivation to learn, transformational leadership and knowledge sharing mediation to increase employee innovative behaviour at PT. Indonesia Power Suralaya Power Generation Unit. Research limitations: The limitation in conducting this research is to explore motivation to learn, transformational leadership mediated by knowledge sharing to increase employee's innovative behaviour. Design/methodology/approach: The quantitative method using a questionnaire with a 10-point Likert scale was used as a research method. The sampling technique was done by simple random sampling. The number of samples used as many as 63 samples to test four (4) hypotheses that have been determined. In testing the statistical significance of the path coefficient, the Structural Equation Modelling model was used. Findings: From the research, it was found that motivation to learn had a significant positive effect on innovative behaviour. Motivation to learn has a negative and insignificant effect on knowledge sharing. Transformational leadership has a significant positive effect on knowledge sharing. And knowledge sharing has a significant positive effect on innovative behaviour. The implications of the findings explain that transformational leadership mediates knowledge sharing so that innovative behaviour increases and motivation to learn has a direct influence on increasing innovative behaviour.